Home environment and nutritional status mitigate the wealth gap in child development: A longitudinal study in Vietnam - Tran, Lan Mai; Nguyen, Phuong Hong; Young, Melissa F.; Ramakrishnan, Usha; Alderman, Harold (Springer, 2023)
Background: Inequity in child development is found at early age, but limited evidence exists on whether these gaps change over time and what are the mediators. Objective: We aim to (1) quantify wealth related gaps in cognitive and socio-emotional development in early and middle childhood; (2) examine how these gaps were mitigated by maternal, child factors and home environment. Methods: We assessed the offspring of women who participated in a randomized controlled trial of preconception micronutrient supplementation in Vietnam (n = 1599). Child development was measured by the Bayley Scales of Infant Development-III (at 1-2y) and the Wechsler Intelligence Scale for Children®—IV (at 6-7y). We used multivariable regression to estimate the changes in wealth gaps for child development over time, adjusting for potential factors that potentially influence cognitive development. Results: We found significant wealth gaps in cognitive development during early childhood (gaps between top and bottom quintiles: 0.5 SD); these gaps increased substantially in middle childhood (0.9 SD). Wealth disparity in social emotion did not change over time (0.26–0.28 SD). Maternal factors, quality of home environment, and child nutritional status mitigated the wealth gap in cognitive development (7-42%) in early childhood. The contribution of these mitigating factors was smaller in middle childhood (2- 15%). Wealth gap in social emotion reduced by 13% and 43% among children with better nutritional status at 2y and higher quality of home environment at 6-7y, respectively. Conclusion: Interventions focusing on improving quality of home environment, maternal education, wellbeing, and child nutrition status may help reduce developmental deficits associated with poverty.